PEMENUHAN HAK ANAK SEBAGAI KORBAN PENELANTARAN OLEH ORANG TUA AKIBAT PERCERAIAN (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The survival of every human being will be through marriage but there are some who cannot continue family relationships and decide to separate. Divorce that often occurs has an impact on children. The issues to be discussed in this research are related to post-divorce child custody of parents and the form of legal protection for fulfilling children's rights after divorce. This study uses a normative legal method where data is obtained through a literature study by studying various references and the results of previous studies. Children do not get their rights after their parents experience a divorce, while children who are born into the world have the right to get rights without being asked. The number of children whose rights are not properly fulfilled. Based on the results of the research and discussion, the researcher can conclude that post-divorce child custody is included in the obligations of both parents. Then related to the fulfillment of children's rights after the divorce of parents, there is a need for protection efforts. The legal basis for child protection in Indonesia is contained in Law Number 4 of 1979 concerning Child Welfare and Law no. 23 of 2002 concerning Child ProtectionKeywords: Divorce, Children's Rights, Child protection